Marianne Werefkin and the Women Artists in Her Circle - Malycheva, Tanja; Wünsche, Isabel (Avant-Garde Critical Studies, 2016)
The volume traces the relationships between Marianne Werefkin and the women artists in her circle. Specifically focusing on issues of cosmopolitan culture, transcultural dialogue, gender roles, and the building of new artistic networks, it re-evaluates the contributions of these artists to the development of modern art. Readership: All interested in 20th-century art, European modernism and the avant-garde movements, specifically women artists. Relevant also for advanced undergraduate and graduate courses in art history, cultural history, German and Slavic studies, and gender studies as well as an international audience of scholars and museum experts.